Experimental hybridization of Coelomomyces dodgei and Coelomomyces punctatus - Federici, Brian A. (1979)
Two closely related fungi, Coelomomyces dodgei and C. punctatus (Chytridiomycetes; Blastocladiales), showing considerable potential for mosquito control, have been hybridized. Both species have life cycles involving an obligate alteration of sexual and asexual generations between an intermediate copepod host and a definitive mosquito host, respectively. Hybridization was accomplished by making reciprocal crosses of gametes derived from infected copepods. In both cases, C. dodgei [unk] × C. punctatus [unk] and C. punctatus [unk] × C. dodgei [unk], zygotes infective for mosquito larvae were formed. Most sporangia produced by the hybrids in infected larvae were not typical of either parental species but resembled C. dodgei more than C. punctatus. Additionally, the majority of the sporangia formed in several larvae exhibited surface structures similar to C. lativittatus, indicating this species may be a naturally occurring hybrid of C. dodgei and C. punctatus. The experimental methods described provide a system to aid in the study of taxonomic relationships among closely related species of Coelomomyces, and furthermore they may contribute to the development of strains efficacious for mosquito control.